Analysis Of Precaution And Consumer Attitudes Towards Motivation-Mediated Decisions Making (Online Product Case Study) - Sutrisno; Mesra B; Nurafrina Siregar (Yayasan Multidimensi Kreatif, 2024)
This study aims to test and analyze the influence of preferences and attitudes on online purchase motivation. Testing and analyzing the influence of attitudes on online purchase motivation. Testing and analyzing the influence of preferences and attitudes on online purchases. This type of research is quantitative. Data analysis technique using SEM-PLS. The sample used in this study was 67 respondents. The results of the study show that customer preferences have a positive and significant effect on consumer motivation. Consumer attitudes have a positive and significant effect on consumer motivation. Consumer motivation has a positive and significant effect on online purchase decisions. Preferences have a positive and significant effect on online purchase decisions. Consumer attitudes have a positive and significant effect on online purchase decisions. Consumer preferences have a positive and significant effect on online purchase decisions through motivation. Consumer attitudes have a positive and significant effect on online purchase decisions through motivation.